(untitled) - Van Vuuren, Elizabeth (Stellenbosch : Stellenbosch University)

Blurred lines : exploring the convergence of gaming and filmic storytelling, and the role of viewer/player agency (2025)
Thesis (MA)--Stellenbosch University, 2025.